ATP‐Releasing Nucleotides: Linking DNA Synthesis to Luciferase Signaling. (6th January 2016) - Ji, Debin; Mohsen, Michael G.; Harcourt, Emily M.; Kool, Eric T.
Abstract: A new strategy is reported for the production of luminescence signals from DNA synthesis through the use of chimeric nucleoside tetraphosphate dimers in which ATP, rather than pyrophosphate, is the leaving group. ATP‐releasing nucleotides (ARNs) were synthesized as derivatives of the four canonical nucleotides. All four derivatives are good substrates for DNA polymerase, with K m values averaging 13‐fold higher than those of natural dNTPs, and k cat values within 1.5‐fold of those of native nucleotides. Importantly, ARNs were found to yield very little background signal with luciferase. DNA synthesis experiments show that the ATP byproduct can be harnessed to elicit a chemiluminescence signal in the presence of luciferase. When using a polymerase together with the chimeric nucleotides, target DNAs/RNAs trigger the release of stoichiometrically large quantities of ATP, thereby allowing sensitive isothermal luminescence detection of nucleic acids as diverse as phage DNAs and short miRNAs.